Nanoparticle size-fractionation through self-standing porous covalent organic framework films - Dey, Kaushik; Kunjattu, Shebeeb H.; Chahande, Anurag M.; Banerjee, Rahul (Angewandte Chemie-International Edition, 2020)
Covalent organic frameworks (COFs) have attracted attention due to their ordered pores leading to important industrial applications like storage and separation. Combined with their modular synthesis and pore engineering, COFs could become ideal candidates for nanoseparations. However, the fabrication of these microcrystalline powders as continuous, crack-free, robust films remains a challenge. Herein, we report a simple, slow annealing strategy to construct centimeter-scale COF films (Tp-Azo and Tp-TTA) with micrometer thickness. The as-synthesized films are porous (SA(BET)=2033 m(2) g(-1) for Tp-Azo) and chemically stable. These COFs have distinct size cut-offs (ca. 2.7 and ca. 1.6 nm for Tp-Azo and Tp-TTA, respectively), which allow the size-selective separation of gold nanoparticles. Unlike, other conventional membranes, the durable structure of the COF films allow for excellent recyclability (up to 4 consecutive cycles) and easy recovery of the gold nanoparticles from the solution.
Keywords: covalent organic frameworks; films; nanofilter; Nanoparticles; size-selective separation